2011
DOI: 10.1111/j.1600-0897.2011.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Immune Maturation and Allergy Development: Regulation by Maternal Immunity and Microbial Exposure

Abstract: Citation Jenmalm MC. Childhood Immune Maturation and Allergy Development: Regulation by Maternal Immunity and Microbial Exposure. Am J Reprod Immunol 2011; 66 (Suppl. 1): 75–80Problem  The increasing allergy prevalence in affluent countries may be caused by reduced microbial stimulation, resulting in an abnormal post‐natal immune maturation. Most studies investigating the underlying mechanisms have focused on post‐natal microbial exposure. Also, the maternal microbial environment during pregnancy may program t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 74 publications
(98 reference statements)
4
67
0
Order By: Relevance
“…The observation of maternal allergy as a more significant risk factor for allergy development in the offspring as compared with paternal allergy [159][160][161] has shed more light on the pregnancy as an important time period for fetal immune development [162]. The immunological mechanisms behind this phenomenon are not known, but indicate an influence of the maternal immunity on allergy development, besides the contribution of the genes.…”
Section: Immunological Interactions Between Mother and Child During Pmentioning
confidence: 99%
“…The observation of maternal allergy as a more significant risk factor for allergy development in the offspring as compared with paternal allergy [159][160][161] has shed more light on the pregnancy as an important time period for fetal immune development [162]. The immunological mechanisms behind this phenomenon are not known, but indicate an influence of the maternal immunity on allergy development, besides the contribution of the genes.…”
Section: Immunological Interactions Between Mother and Child During Pmentioning
confidence: 99%
“…The mean ILC2 proportions were very similar in children developing allergy or staying healthy according to our strict criteria, however. Previously, it has been shown that children who later develop allergic disease have a more pronounced T H 2 deviation already at birth, 4 with enhanced circulating T H 2-associated chemokine levels, 5 which would suggest a role for increased ILC2 proportions in neonates later developing allergies. However, the involvement of ILC2 in allergic disease has primarily been observed at effector sites, that is, at mucosal surfaces.…”
Section: To the Editormentioning
confidence: 99%
“…However, previous studies have demonstrated the crucial function of GATA-3 in ILC2 since ectopic expression of GATA-3 in human Lin(2)CD127(1)CRTH2(2) cells resulted in induction of CRTH2 and the capacity to produce high amounts of type 2 cytokines in response to thymic stromal lymphopoietin plus IL-33. Because a more pronounced T H 2 deviation is suggested to precede the development of allergic disease 4 and ILC2 have been implicated to be involved in allergic responses, 1,2 we investigated whether high ILC2 proportions in cord blood could predict the development of allergic disease. However, no differences were detected in cord blood between children who later developed allergic diseases and those who remained nonallergic up to the age of 6 years (Table I) (percentages of ILC2 among lymphocytes: mean, 0.10 6 0.03, n 5 7, and mean 0.09 6 0.02, n 5 7, respectively).…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The intestine provides a unique environment for the development of both immunity and tolerance, and the initiated immune response is dependent on DC type and state of activation. The probiotic supplementation during pregnancy and early childhood could possibly provide microbial stimulation needed for normal development of immunoregulatory capacity, providing a source of TLR-ligand exposure [37,38].…”
Section: Probiotics and Immune Regulationmentioning
confidence: 99%